PENINGKATAN PEMAHAMAN POLA HIDUP SEHAT SEJAK USIA DINI : STUDI KASUS PADA SISWA/I MIN 14 AL-AZHAR ASY- SYARIF INDONESIA - Restu, Andhika Hartian; Sari , Imelda Yunita; Amelia , Kirana; Nainggolan , Nancy Tarina; Mulyadi, Mulyadi; Subakdi, Subakdi; Halim , Abdul; Bramantyo , Andreas; Manalu , Ronald (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
A healthy lifestyle is an essential component that should be instilled from an early age. To create a successful generation capable of advancing Indonesia, maintaining the quality of public health is crucial. Various practices can be implemented to promote clean and healthy living habits, starting with small steps, such as getting used to washing hands before any activity, especially before meals, consuming a balanced diet according to the “Four Healthy, Five Perfect” guideline, and maintaining oral and dental hygiene. However, awareness of the importance of a healthy lifestyle has not yet been fully optimized within society. Many individuals understand the concept of a healthy lifestyle but lack knowledge of the correct practical steps. Therefore, this community service aims to educate elementary school students to help them understand and implement proper steps in practicing a healthy lifestyle. The method chosen for this socialization includes lectures and question-and-answer sessions, conducted at MIN Al-Azhar As-Syarif Indonesia